2022
DOI: 10.1017/jfm.2022.179
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of homogeneous and isotropic turbulence in emulsions

Abstract: We present a numerical study of emulsions in homogeneous and isotropic turbulence (HIT) at $Re_\lambda =137$ . The problem is addressed via direct numerical simulations, where the volume of fluid is used to represent the complex features of the liquid–liquid interface. We consider a mixture of two iso-density fluids, where fluid properties are varied with the goal of understanding their role in turbulence modulation, in particular the volume fraction ( $0.03<\alpha &l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
53
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 64 publications
(240 reference statements)
14
53
0
1
Order By: Relevance
“…This method combines the exact mass conservation properties of certain geometric VoF methods with the reduced number of local operations for the interface reconstruction of the algebraic VoFs, making it a good candidate for properly exploiting hybrid and accelerated architectures. The version available in our group has been validated in [34] and extensively employed in a different variety of multiphase configurations, both for laminar [35,36,37] and turbulent [38,39,40,41] flows. Note that it has been extended to phase changing flows [42] and also to handle weakly compressible multiphase flows (low-Mach approximation) [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…This method combines the exact mass conservation properties of certain geometric VoF methods with the reduced number of local operations for the interface reconstruction of the algebraic VoFs, making it a good candidate for properly exploiting hybrid and accelerated architectures. The version available in our group has been validated in [34] and extensively employed in a different variety of multiphase configurations, both for laminar [35,36,37] and turbulent [38,39,40,41] flows. Note that it has been extended to phase changing flows [42] and also to handle weakly compressible multiphase flows (low-Mach approximation) [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…By fitting experimental data, Deane and Stokes [ 19 ] proposed a d −3/2 power law in this region. Recent numerical studies [ 16,17,25 ] adopted these power laws for emulsions and observed a good agreement for dense emulsions, especially for d < d H . Although a lot of studies have already investigated droplet size distributions, certain aspects are still not yet clarified.…”
Section: Introductionmentioning
confidence: 97%
“…Recently a finite‐volume approach has been employed to study emulsions. Using the volume of fluid method (VOF), Crialesi‐Esposito et al [ 17 ] studied the effect of variations in the viscosity ratio, the volume fraction, and the surface tension on size distributions and the energy transport between different scales. The emulsification process, that is, the breakup of a liquid structure in HIT, was also the focus of various numerical investigations, such as, for example, Komrakova et al [ 33 ] , Komrakova, [ 34 ] Zhong and Komrakova [ 35 ] using a free‐energy LBM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations